PENGARUH IMPLEMENTASI RELATIONSHIP MARKETING TERHADAP CUSTOMER LOYALTY - Erida .; Anggia Agustini Saputir (DIGEST MARKETING, 2017)
The purpose of this research is to analyze the influence Marketing Relationship Implementation on customer loyalty and to explain the variable of marketing relationship that dominantly influencing. This research has done at Bank Mandiri Micro Business Cluster Jambi 1. The research variable is:Marketing Relationship that consists ofpeople, knowledge and insight, process and technology for is treated as independent variable, and Customer Loyalty as dependent variable. Based on research resultit is knownthat the influence of marketing relationship has significant on customer loyalty where Pvalue = 0,000 < α = 0, 05. The ability to explain dependent variable that shows by R is 0,510 or 51%. And partially, all of variables have the significant influence. But the absolutely dominant variable is knowledge and insight and the smallest influence is process. This condition is Bank Mandiri Micro Business Cluster 1 must be able to maintain and pay attention to each of all variables that influent customer loyalty to be continual in making the relationship for the long range with the debtor. Key words : People, process, technology, and loyalty, Micro Business Cluster